2012
DOI: 10.1037/a0028638
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of acculturative stress on body image disturbance among Hispanic college students.

Abstract: This study investigated the impact of acculturative stress on psychological well-being and body image disturbance in a sample of female and male Hispanic individuals. The unique protective effects of differing social support sources, including family and peer support, were examined against acculturative stress and body image disturbance. A total of 399 participants of Hispanic origin were recruited from Texas Tech University in West Texas. Students completed a battery of measures of acculturative stress and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 63 publications
2
34
1
Order By: Relevance
“…Less time in the U.S. has been associated with decreased social ties among Latino immigrants [33]. However, social support has been found to be an important mitigating factor in buffering acculturative stress among Latino immigrants [34]. Investment in social relations facilitates the flow of information [35], making the acculturation process less difficult and stressful.…”
Section: Introductionmentioning
confidence: 99%
“…Less time in the U.S. has been associated with decreased social ties among Latino immigrants [33]. However, social support has been found to be an important mitigating factor in buffering acculturative stress among Latino immigrants [34]. Investment in social relations facilitates the flow of information [35], making the acculturation process less difficult and stressful.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the sources used a proxy measure (years lived in the US) to assess acculturation, which has been criticized in conjunction with immigrant generational status for being insensitive to the capturing of the attitudinal and behavioral change processes implicit in the acculturation experience . Emerging literature among immigrant and ethnic‐minority adults supports the further exploration of the behavioral and psychological domains of acculturation—particularly acculturative stress . Only by paying appropriate attention to these constructs can we adequately disaggregate the extent to which aspects of the immigrant experience exacerbate or attenuate the risk for BID and eating disorders among immigrant children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent work has suggested that the stress associated with acculturation ( acculturative stress ) can place immigrants at greater risk for BID and eating disorder concerns. Specifically, the perception that one needs to conform to the body expectations of a particular culture in order to “fit‐in” may create a heightened vulnerability for the internalization of sociocultural pressures for weight and shape, which may increase the risk for BID . However, the extent to which acculturation and acculturative stress have been examined in relation to BID among immigrant children and adolescents is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns of results, referred to as the immigrant paradox , are also present in Hispanic/Latino populations (Alarcón et al, ). For example, Hispanic/Latino men and women who are more acculturated are more likely to be diagnosed with a psychiatric disorder (Coll & Marks, ), to endorse LOC eating (Alegria et al, ), and to have greater body image concerns (Menon & Harter, ), and a higher BMI (Delavari, Sønderlund, Swinburn, Mellor, & Renzaho, ). Acculturation‐related stressors relevant to body image concerns and LOC eating may include Western appearance ideals that value thinness and muscularity (Schaefer et al, ).…”
Section: Relevant Identity Factors: Acculturation and Ethnic Identitymentioning
confidence: 99%